The inclusion ranges and extent of the Sustainable Development dimensions in the of the Hadith (Prophet’s Traditions) and the Biography of the Prophet Curriculum, for the fifth grade of primary school in the Kingdom of Saudi Arabia - Al-Elaiwi, Huda Daloh; Al-Saeed, Hanaa Suleiman; Al-Saif, Abdul Mohsen Saif (Journal of Educational and Psychological Sciences, 2022)
The research aimed to reveal the inclusion range and extent of the Sustainable Development dimensions in the Hadith (Prophet’s Traditions) and the Biography of the Prophet Curriculum, for the fifth grade of primary school in the Kingdom of Saudi Arabia, and to reveal the level of inclusion of each dimension (Social, Economic and Environmental). The descriptive analytical approach was used, using the content analysis method. The research elements consisted of books of Hadith (Prophet’s Traditions) and biography of the Prophet for the fifth grade of primary school in the Kingdom of Saudi Arabia, which consisted of (2), and the sample represented all the elements. A content analysis card was used which is consistent of the Sustainable Development dimensions (social, economic, and environmental), and each dimension included sub-indicators, and the total number of indicators reached (26). The results of the research revealed that the percentage of Sustainable Development dimensions included in the Hadith (Prophet’s Traditions) and the Biography of the Prophet Curriculum for the fifth grade came at a varying rate. The social dimension was the most included with a percentage (73.55%), and the number of repetition amount reached (1068). Followed by the economic dimension, in which the inclusion rate reached (20.32%) and a number of repetition amount reached (295). Finally, the environmental dimension appeared with an inclusion rate of (6.13%) and a number of repetition amount (89), and it was noted that it is a very weak percentage. The study came up with recommendations, the most important of which are: First, the need to take notice of the relative balance to include the Sustainable Development dimensions in the Hadith (Prophet’s Traditions) and the Biography of the Prophet Curriculum, so that one dimension does not overpower the rest of the dimensions. Second, focus on enriching the Hadith (Prophet’s Traditions) and the Biography of the Prophet Curriculum of the fifth grade with activity supplementary lessons that enhance the areas of Sustainable Development, specifically the environmental field.